Studying Balance in Deaf People: A Systematic Review Study - Ali Asghar Norasteh; Hamed Zarei (University of Social Welfare and Rehabilitation Sciences, 2019)
Objective Damage to parts of the vestibulocochlear nerve not only results in sensory-neural hearing loss and deafness but may also lead to balance problems. This is the reason why the hearing-impaired and deaf people are struggling with balance problems. Given the ever-increasing development of the adaptive sports, specific to the deaf, who are considered as part of the active individuals in the community, detailed studies are required on the balance of the deaf, which is an important part of routine activities and sports performances. Therefore, this study generally aims to investigate the balance skills of the deaf in comparison to their normal counterparts. Materials & Methods In this study, a comprehensive review on 'the balance of the deaf' has been carried out by searching English databases, such as Science Direct, PubMed, Cochrane review, TRIP, PEDro, EMBASE, CINAHL, and Google Scholar, for the following keywords: "Deaf", "Postural control in Deaf Hearing Loss", "Deafness", "Balance" and "Balance in Deaf". In addition, the Persian databases, such as Magiran, Irandoc, IranMedex, MedLib, Sid were searched for the following Persian equivalent keywords: Balance in the deaf, postural control in the deaf, deaf, congenital deafness and balance, from 1932 to June 2018. Moreover, manual searching and full reviewing of resources of the articles were carried out to find the respective articles. Articles were narrowed down and sorted out by the titles such as the English language, Persian language, Human, original article, and review article. After collecting the search results, the titles and abstracts of the articles were studied. If the articles met the inclusion and exclusion criteria, their results would be employed in the review study; otherwise, they would be excluded. Results Based on the criteria and objectives of the research, 51 articles were selected. Forty-eight papers were provided in full text and the rest were summarized. In general, the balance of the deaf was investigated in three different respects of 1) a comparison of the balance of the deaf with that of the normal counterparts, 2) the effect of age on the balance of the deaf, and 3) the effect of the training protocols on the balance of the deaf. Conclusion The deaf people appear to struggle with balance problems when the vestibular system information is the only sensory source available; however, when the information of the proprioception and vision systems is available, there can be no balance problem as compared to normal counterparts. Several studies have also shown that the deaf, as they age, make up for the balance impairment resulting from vestibular impairments with proprioception and vision systems; it also appears that their proprioception and vision systems are better than or equal to those of their normal counterparts. However, it has not been determined yet that by increasing age in the deaf people, which proprioception system dominates and contributes to maintaining the balance of the deaf better than other systems. Furthermore, a review of studies has shown that all training programs and rehabilitation protocols have positive effects on the balance of the deaf. However, it has not been determined yet which training programs have a long and lasting effect on the balance of the deaf, and few studies have been carried out in this area. In addition, the same balance tests are used in all community groups, which may be inappropriate for measuring the balance in deaf people, since it is still not clear which motion strategies have been employed by the deaf to maintain balance. Therefore, to reach the final conclusion about the balance of the deaf people, further studies should be conducted on the proper tests to measure the balance of the deaf so that accurate and high-quality reports on their balance can be obtained.